2013
DOI: 10.7241/ourd.20131.01
|View full text |Cite
|
Sign up to set email alerts
|

Some modifications in transplantation of autologus non -cultured melanocytes-keratinocytes suspension in treatment of segmental and focal vitiligo (Egyptian Experience in Alexandria University)

Abstract: Introduction: Transplantation of Autologous non-cultured melanocytes suspension is a simple yet effective cell-based therapy for vitiligo. Materials and Methods: 20 patients with stable vitiligo were subjected to epidermal cell suspension transplantation using Osslon's method with some new modifications. Result: The repigmentation at 7 of the test sites (35.0%) was excellent. It was good for more than half of the test sites (55.0%). Fair repigmentation was encountered among only 2 (10.0%) of the tested sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…Munish's 4 study revealed excellent color matching in 79% patients. Color match was same as that of the surrounding normally pigmented skin in majority of patients, 90.0%, in a study by Sobhy et al 11 conducted among 20 stable vitiligo patients. In a study done by Huggins et al 12 with 29 treated lesions, good color match was noted in 62% of cases.…”
Section: Jmedsmentioning
confidence: 59%
“…Munish's 4 study revealed excellent color matching in 79% patients. Color match was same as that of the surrounding normally pigmented skin in majority of patients, 90.0%, in a study by Sobhy et al 11 conducted among 20 stable vitiligo patients. In a study done by Huggins et al 12 with 29 treated lesions, good color match was noted in 62% of cases.…”
Section: Jmedsmentioning
confidence: 59%
“…Sobhy et al [11], also reported earlier repigmentation and better prognosis in age group<15 years than in older patients, probably due to younger cell that grows and multiplies rapidly.…”
Section: Age At Presentation Versus Extent Of Pigmentation At 6 Monthsmentioning
confidence: 91%
“…Verma et al [12], in their study, non-cultured melanocyte technique group included 47.4% (9) females and 52.6% (10) males while Sobhy et al [11] study showed 13 female and 7 male patients.…”
Section: Sexmentioning
confidence: 92%
See 2 more Smart Citations